Hydrodynamic measurements around moving profiles: Flapping flight, water turbine, and oscillating profile - David, L.; Bernard, A.; Chatellier, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
In the field of the fluid mechanics, the team HYDEE (Hydrodynamics and Environmental flow section) of the institute Pprime is involved in the understanding of flows around moving profiles for environmental applications, the maritime transport, the renewable energy production, The research interests cover fundamental aspects of unsteady flows with moving structures, turbulent free-surface flows, environmental flows and mixing through different national and European programs. Fundamental contributions to optical flow measurements include PIV stereoscopy PIV measurement techniques and recently free surface measurement and volumetric measurement techniques have been obtained.